(untitled) (Indian Journal of Public Health Research & Development, 2020)
The main aim of this review is to understand the changes in oral mucosa during pregnancy. This review highlights the major oral complication during pregnancy. Changes in the gingiva and physiological structure of the tooth take place in addition to hormonal, immunologic, dietary and behavioural changes. Characteristics of pregnancy gingivitis are that it gets swollen, smooth and tends to bleed easily. Enlargement of gingiva may occur but it tends to resolves within few months after delivery. Due to the increase in salivary microorganisms, there may be a decrease in salivary pH and impairment of buffer effect. This may also lead to dental caries or erosion during lactation period. The dental management of pregnant patients requires special attention. Dentists, for example, may delay certain elective procedures so that they coincide with the periods of pregnancy which are devoted to maturation versus organogenesis. At other times, the dental care professionals need to alter their normal pharmacological armamentarium to address the patients’ needs versus the foetal demands. Applying the basics of preventive dentistry at the primary level will broaden the scope of the prenatal care. Dentists should encourage all the patients of the childbearing ages to seek oral health counselling and examinations as soon as they learn that they are pregnant